PENEGAKAN HUKUM ATAS PENCATATAN HAK CIPTA SOFTWARE OLEH PENGGARAP CIPTAAN DITINJAU DARI UU HAK CIPTA: Studi Putusan Nomor 60/Pdt.Sus-HakCipta/2020/PN.Niaga.Jkt.Pst - Figo Alay Ghazi, (2023)
Software (Software) is a type of creation resulting from the reflection of the creator in the fields of technology, communication and information. Furthermore, software creations are creations that require protection because they are part of the exclusive property and rights of the creator of the work. This study aims to find out how law enforcement is and how the perpetrators are held accountable in cases of cultivators who register their software illegally. In the review of the Decision: No. 60/Pdt.Sus-HakCipta/2020/PN.Niaga.Jkt.Pst by applying the provisions of Law Number 28 of 2014 concerning Copyright. Qualitative research methods were also used in this study. The results of this study indicate that copyright law regulates how software becomes part of the exclusive rights and property rights of the creator, based on the judge's considerations in deciding the case. Therefore, parties involved in violations of procedures for registering works that are not original must be held accountable in accordance with a judge's decision, in accordance with the applicable provisions, namely Law Number 28 of 2014 concerning Copyright.